Associations between maternal BMI, breastfeeding practices and infant anthropometric status in Colombia; secondary analysis of ENSIN 2010 - Fanny Aldana-Parra; Gilma Olaya Vega; Mary Fewtrell (BMC, 2020)
Abstract Background Maternal malnutrition and infant feeding mode impact short and long term infant and child morbidity and mortality. The period of lactation may provide an opportunity to modulate the risk of disease later in life. Our aim was to estimate the effect of maternal body mass index (BMI) and infant feeding mode, particularly breastfeeding practices, on the anthropometric status of children under 2 years in Colombia. Methods A secondary analysis was performed using the data from ENSIN 2010. Term infants under 2y, singleton, with a mother older than 18y, were included in the analysis. Outcomes were wasting (WLZ < -2SD), overweight (WLZ > +2SD) and stunting (LAZ < -2SD). Predictors were infant feeding (exclusive and predominant BF constructed from 24-h recall, age at introduction of liquids, semisolids and solids) and maternal BMI. Socioeconomic variables, maternal education and age, conditions during pregnancy and birth weight were analyzed as covariates. Results Mothers of overweight infants had higher BMI (Mean dif = 1.47 kg/m2; 95% CI = 2.1, 0.8) than those with normal weight infants. Stunting and wasting were not predicted by maternal anthropometry or infant feeding mode. Fewer maternal years of education were associated with wasting (OR = 0.90; 95% CI = 0.86, 0.97; p = 0.003) and stunting (OR = 0.92; 95% CI = 0.89, 0.94; p < 0.0001), while more maternal years of education were associated with overweight (OR = 1.06; 95% CI = 1.02, 1.01; p = 0.001); higher birth weight was associated with overweight (OR = 1.001; 95% CI = 1.00, 1.001; p < 0.0001) and lower birth was associated with stunting (OR = 0.99; 95% CI = 0.89; p < 0.0001) in the final regression model. Conclusions Maternal BMI is a modifiable target for public health policy to promote healthy infant growth. Infant nutritional status is affected by direct and indirect factors that need to be addressed in further studies.